MAINTENANCE OF PHYSICAL FITNESS AND ITS INEVITABILITY WITH REFERENCE TO PROPER MANAGEMENT OF LIFE - Gour Gopal Banik (Veda Jyotih: Jurnal Agama dan Sains, 2024)
Body and mind are the two inseparable ingredients of life. Mind is something invisible but its existence can never be denied. The mind is something which thinks, imagines, wishes, senses, remembers and forgets. It is connected with peace, pleasure, pain, perception, belief, emotion, intension, desire and the ultimate decision-making process. In every case, the mind matters the most. A sound mind is of utmost necessity in the proper management of life; and a sound mind is always available only in a sound body. Hence, for maintaining the soundness of mind, the body should be sound and for maintaining the soundness of the body, physical exercise is inevitable. Physical exercise may be of different types which include games and sports, yoga, gymnastics, swimming, running, jogging, cycling and so on and so forth.This paper focuses on the inevitability of physical fitness in the proper management of life.